Screening key genes and miRNAs in early-stage colon adenocarcinoma by RNA-sequencing - Jixi Liu; Fang Liu; Xiaoou Li; Xin Song; Lei Zhou; Jianzheng Jie (Tumor Biology, 2017)
Colon adenocarcinoma is the third leading cause of cancer-related deaths across the world, developing novel and non-invasive diagnostic and prognostic biomarkers for the early-stage colon adenocarcinoma at molecular level is essential. In our study, RNA-sequencing was performed to identify the differentially expressed genes and miRNAs (DEmiRNAs) in early-stage colon adenocarcinoma compared to tissues of precancerous lesions, colonic intraepithelial neoplasia. The DEmiRNA-target interaction network was constructed and functional annotation of targets of DEmiRNAs was performed. The Cancer Genome Atlas was used to verify the expression of selected differentially expressed genes. The receiver operating characteristic analyses of selected differentially expressed genes was performed. In total, 865 differentially expressed genes, 26 DEmiRNAs, and 329 DEmiRNA-target pairs were obtained. Based on the early-stage colon adenocarcinoma network, miR-548c-5p, miR-548i, and miR-548am-5p were the top three DEmiRNAs that covered most differentially expressed genes. NTRK2, DTNA, and BTG2 were the top three differentially expressed genes regulated by most DEmiRNAs. Cancer and colorectal cancer pathways were two significantly enriched pathways in early-stage colon adenocarcinoma. The common differentially expressed genes in both the pathways were AXIN2, Smad2, Smad4, PIK3R1, and BCL2. The expression levels of eight differentially expressed genes (NTRK2, DTNA, BTG2, COL11A1, Smad2, Smad4, PIK3R1, and BCL2) in The Cancer Genome Atlas database were compatible with our RNA-sequencing. All these eight differentially expressed genes and AXIN2 had the potential diagnosis value for Colon adenocarcinoma. In conclusion, a total of ten differentially expressed genes (NTRK2, DTNA, BTG2, COLCA1, COL11A1, AXIN2, Smad2, Smad4, PIK3R1, and BCL2) and four DEmiRNAs (miR-548c-5p, miR-548i, mir-424-5p, and miR-548am-5p) may be involved in the pathogenesis of early-stage colon adenocarcinoma which may make a contribution for developing new diagnostic and therapeutic strategies for early-stage colon adenocarcinoma.